Proyecto experimental de arte público ‘Espacios para el arte’ (Papeles, 2012)
This research project “Spaces for art”, is the result of teaching experience developed as an artist. Applying research-creation processes to transforming artistic preconceptions about teaching of arts in the school context. By designing and developing a draft public art as a strategy to strengthen the visual arts emphasis inside IED Sierra Morena starting with a more flexible curriculum that promotes contemporary art teaching, creatively addressing a specific problem: the difficulties of physical spaces, contextual and pedagogical to expression of the visual arts into schools. The approach of the students to the language of contemporary art, the interventions ephemeral and permanent transformation of common places, allowed them to present the results in arts festivals during to 2010.
Keywords: autonomy; self-regulation; technology and computer science; robotics